2012
DOI: 10.1002/jbt.21416
|View full text |Cite
|
Sign up to set email alerts
|

Study on organochlorine pesticide levels in chronic kidney disease patients: Association with estimated glomerular filtration rate and oxidative stress

Abstract: Nephrotoxicity of organochlorine pesticides (OCPs) has been established in experimental animal models. This study was designed to evaluate the relationship of the blood OCPs level with the estimated glomerular filtration rate (eGFR) and oxidative stress (OS) in chronic kidney disease (CKD) patients. Patients in different stages of CKD (n = 150) and age, sex matched healthy controls (n = 96) were recruited. The blood OCPs level were analyzed by gas chromatography, and plasma levels of several OS parameters such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 28 publications
0
36
0
1
Order By: Relevance
“…Recently, it was shown that 12 mo of combined probiotic and prebiotic treatment improved glomerular filtration rate better than a low protein diet (138). A reduced glomerular filtration rate can lead to the accumulation of toxins in the body (139).…”
Section: Df Kidney Function and Nitrogen Metabolismmentioning
confidence: 99%
“…Recently, it was shown that 12 mo of combined probiotic and prebiotic treatment improved glomerular filtration rate better than a low protein diet (138). A reduced glomerular filtration rate can lead to the accumulation of toxins in the body (139).…”
Section: Df Kidney Function and Nitrogen Metabolismmentioning
confidence: 99%
“…9,33 This is relevant also in the Indian context because recent studies from Northern India have shown elevated urinary levels of organochlorine pesticides in patients with CKD of both known and unknown causes. 34,35 The nephrotoxic role of silica through the enteral route also needs to be probed given a recent cross-sectional study from a CKD endemic village in Southern India showing significantly higher silica and strontium levels in drinking water. 36 Typically, silica nephrotoxicity has been reported from occupational silica dust exposure and is a secondary glomerular disease from autoimmune diseases that are promoted by silicosis, such as SLE (systemic lupus erythematosus), Goodpasture syndrome, polyarteritis nodosa, and ANCA (antineutrophil cytoplasmic antibody)2associated vasculitis.…”
mentioning
confidence: 98%
“…The authors also observed a tendency to accumulate pesticides by the CKD patients with decreasing eGFR. They also demonstrated a significant association of total pesticide load with increased oxidative stress in CKD patients [56]. In a previous study by the same authors from the same laboratory showed that the increased OCP levels in CKD patients were partially dependent on GSTM1/GSTT1 polymorphism and particularly GSTM1 (−)/GSTT1 (−) genotype was more vulnerable in this regard [66].…”
Section: Ocps Exposure and Ckdumentioning
confidence: 88%
“…Published data on the level of OCPs from the blood samples of general population from different parts of India have shown the presence of a number of OCPs. The OCPs levels ranged from 2.92 to 4.52 parts per billion (ppb) for α-HCH, 1.93-10.05 ppb for β-HCH, 1.69-5.33 ppb for γ-HCH, 0.03-3.32 ppb for aldrin, 1.97-2.77 ppb for dieldrin, 0.01-2.21 ppb for α-endosulfan, 1.18-1.49 ppb for β-endosulfan, 0.045-1.62 ppb for p,p′-DDT, and 2.18-4.26 ppb for p,p′-DDE [56]. High serum concentration of BHC and DDE (range: 0.006-0.130 ppm for BHC and 0.002-0.033 ppm for DDE) were detected in agro and non-agro professionals in and around Madurai, India [50].…”
Section: Detectable Blood Levels Of Ocps In General Populationmentioning
confidence: 99%